Calcium Dynamics in Vascular Smooth Muscle. (10th May 2013) - Amberg, Gregory C.; Navedo, Manuel F.
Abstract Smooth muscle cells are ultimately responsible for determining vascular luminal diameter and blood flow. Dynamic changes in intracellular calcium are a critical mechanism regulating vascular smooth muscle contractility. Processes influencing intracellular calcium are therefore important regulators of vascular function with physiological and pathophysiological consequences. In this review we discuss the major dynamic calcium signals identified and characterized in vascular smooth muscle cells. These signals vary with respect to their mechanisms of generation, temporal properties, and spatial distributions. The calcium signals discussed include calcium waves, junctional calcium transients, calcium sparks, calcium puffs, and L‐type calcium channel sparklets. For each calcium signal we address underlying mechanisms, general properties, physiological importance, and regulation.